CULTURAL AND MORPHOLOGICAL VARIABILITY OF CORYNESPORA CASSIICOLA (BERK. AND CURT.) WEI. CAUSING TARGET SPOT DISEASE IN COTTON - B. MOHAN VENKATA SIVA PRASAD, BHATTIPROLU, S.L*., V. MANOJ KUMAR, K. JAYALALITHA; D.V. SAI RAM KUMAR (The Journal of Research ANGRAU, 2023)
Cultural and morphological variability of Corynespora cassiicola (Berk. and Curt.) Wei. causing target spot of cotton, was studied on different growth media. Ten different media viz., Potato Dextrose Agar (PDA), Potato Sucrose Agar (PSA), Carrot Dextrose Agar (CDA), Carrot Sucrose Agar (CSA), Oat Meal Agar (OMA), Lactose Casein Agar (LCA), Lactose Peptone Agar (LPA) and different leaf extract media viz., Cotton Leaf Extract Agar (CLEA), Blackgram Leaf Extract Agar (BgLEA), Greengram Leaf Extract Agar (GgLEA) were used to find out the media which enables pathogen to grow fast and to identify the best media for good sporulation. Among the different media tested,CLEA media promotedthe highest radial growth (7.83cm) having more growth rate (0.54 mm per hr) followed by BgLEA with radial growth of 6.80cm and growth rate of 0.47mm per hr; lowest radial growth observed in CAS (4.20 cm) with growth rate of 0.29 mm per hr. Highest sporulation observed in CLEA (394 x104±10.8) followed by LPA (132 x104±22.1) and lowest was observed in GgLEA (11.2 x104±2.8). Conidial morphology varied in the different media tested, lowest conidial length was observed in CLEAmedium(32.83 ±3.33μm) whereas highest in LPA medium(91.58±3.50μm);narrowest conidial width in CLEA medium (7.36±1.79μm) and broadest conidial length in BgLEA medium (12.42±2.02μm).